2011
DOI: 10.1021/jp203398j
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Active Sites in Heterogeneous Alkene Hydrogenation on Platinum Catalysts Revealed by Means of Parahydrogen-Induced Polarization

Abstract: Substantial NMR signal enhancements provided by parahydrogen-induced polarization (PHIP) are associated with the ability of a catalyst to incorporate both H atoms of a dihydrogen molecule into the same product molecule. Therefore, PHIP can provide valuable information about the mechanisms and kinetics of catalytic hydrogenation reactions as well as produce hyperpolarized molecules for sensitivity enhancement in NMR. In this work, the PHIP technique was applied to study the structure sensitivity and the support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
94
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 41 publications
3
94
0
2
Order By: Relevance
“…The major differences in the PHIP effects observed for metal nanoparticles supported on titania relative to those previously observed for metals on other supports [11][12][13] were tentatively attributed to low-temperature SMSI effects. Therefore, in this communication the behavior of titania-supported catalysts is …”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The major differences in the PHIP effects observed for metal nanoparticles supported on titania relative to those previously observed for metals on other supports [11][12][13] were tentatively attributed to low-temperature SMSI effects. Therefore, in this communication the behavior of titania-supported catalysts is …”
mentioning
confidence: 59%
“…[9][10][11] Recently,i tw as shown that the nature of the catalyst support can have as ignificant impact on the rate of the pairwise addition of hydrogen. [12,13] Remarkably,t itania-supported metal catalysts were shown to exhibit much higher levels of the pairwise addition of hydrogen (and larger PHIP effects) relative to that exhibited by metals on other supports. [9,14] Therefore, examination of the nature of the active sites for titania-supported nanoparticles in the contexto ft he pairwise addition of hydrogen may open up new possibilities for the rational preparation of catalysts that are able to maximize the observed PHIP effects and for the production of hyperpolarizedm olecular contrast agents potentially suitable for in vivo magnetic resonance imaging investigations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in principle, the PHIP effect should not be observed in a heterogeneous hydrogenation, but recently PHIP has indeed been observed for this type of reaction [26,27]. This means that pairwise hydrogen addition does take place in this reaction to some extent, but the origin of the PHIP effect is still unclear.…”
mentioning
confidence: 98%
“…The influence of the platinum particle size on the PHIP has been studied in detail for propylene hydrogenation catalyzed by Pt/g-Al 2 O 3 with various metal particle sizes. 673 The dependence of the magnitude of PHIP on the particle size proved to be non-monotonic: the effect was least pronounced for particles of diameter 2 ± 4 nm and increased for both larger and smaller particles (Fig. 30).…”
Section: Studies Of the Mechanisms Of Catalytic Reactions By Thmentioning
confidence: 94%